The Berlin Process in the Western Balkans: Big ideas, difficult implementation - Marina Vulović (Stiftung Wissenschaft und Politik (SWP), 2022)
The Western Balkans should join the European Union (EU) "as soon as possible", according to statements by the Chancellor of Germany at the Berlin Process summit in early November 2022. The Berlin Process consists of a series of events and meetings that have taken place annually since 2014 between individual EU member states and the countries of the Western Balkans. It differs from other EU initiatives in that international financial and EU institutions are involved alongside individual EU states, such as Germany as the format's initiator, and it primarily addresses issues of economic and regional cooperation. Although the Berlin Process has already produced many ambitious ideas, such as the common regional market, the implementation of the agreements by the Western Balkan states has often stalled. In the future, Germany and the EU should insist more emphatically on the implementation of adopted agreements, because the Berlin Process has the potential to restore the decliningress towards disarmament is good news. For Germany's National Security Strategy (NSS), it means that greater concessions to advocates of the TPNW are not necessary to protect the NPT.
Keywords: 320; Berlin Process; Western Balkans; EU accession; Albania; Bosnia and Herzegovina; Kosovo; Montenegro; Serbia; North Macedonia Common Regional Market (CRM); Regional Youth Cooperation Office (RYCO); Western Balkans Investment Framework (WBIF); Regional Economic Area (REA); Civil Society & Think Tank Forum